2007
DOI: 10.1111/j.1742-4658.2007.05900.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Cdc45 is a proliferation‐associated antigen

Abstract: Cell division cycle protein 45 (Cdc45) plays a critical role in DNA replication to ensure that chromosomal DNA is replicated only once per cell cycle. We analysed the expression of human Cdc45 in proliferating and nonproliferating cells. Our findings show that Cdc45 protein is absent from long‐term quiescent, terminally differentiated and senescent human cells, although it is present throughout the cell cycle of proliferating cells. Moreover, Cdc45 is much less abundant than the minichromosome maintenance (Mcm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
66
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 68 publications
11
66
0
Order By: Relevance
“…In contrast, and unlike the embryonic situation, somatic cells have very low levels of Cdc45 even though this is an upper estimate. This is in agreement with another study that found Cdc45 to reside at low levels in human tumor cells [38].…”
Section: Resultssupporting
confidence: 93%
“…In contrast, and unlike the embryonic situation, somatic cells have very low levels of Cdc45 even though this is an upper estimate. This is in agreement with another study that found Cdc45 to reside at low levels in human tumor cells [38].…”
Section: Resultssupporting
confidence: 93%
“…With a nuclear volume of about 500 to 600 fl for the HeLa S3 cells [24] this would yield 10,000 to 20,000 molecules of eGFP-Cdc45 per cell. Our quantitative western blot experiments shown in Figure 1b revealed that the ratio of eGFP-Cdc45 to endogenous Cdc45 is approximately 1 to 4 resulting in an estimate endogenous Cdc45 number of 40,000 to 80,000 molecules per cell, which is in agreement with previous estimated numbers of Cdc45 molecules per cell being 45,000 [28].…”
Section: Resultssupporting
confidence: 90%
“…Antibodies recognizing Cdc45 (C45-3G10-111) [4], p125 of Pol δ (PGD-5E1) [28] and RPA 32 (RBF-4E4) [36], [37]. Anti-Mcm5 antibody was obtained from Prof R. Knippers [38].…”
Section: Methodsmentioning
confidence: 99%
“…As many other DNA replication factors, Cdc45 is more abundant in proliferating cells, whereas it is almost absent from long term quiescent, terminally differentiated, and senescent cells (8). Several genetic studies, two-hybrid screens, and co-immunoprecipitation analyses revealed that Cdc45 interacts with a number of other replication factors, including the Mcm2-7 complex, GINS, MCM10, replication protein A, DNA polymerases ␣, ␦, and ⑀, the origin recognition complex subunit 2, and TopBP1 (for a review see Ref.…”
mentioning
confidence: 99%